A comparative analysis on energy-saving and emissions-reduction performance of three urban agglomerations in China. (20th May 2019) - Tang, Liwei; Li, Ke
Abstract: China's most important three urban agglomerations, the Beijing-Tianjin-Hebei (BTH), Yangtze River Delta (YRD) and Pearl River Delta (PRD), are expected to play a leading role in energy saving and emissions reduction in China. Based on the biennial Malmquist productivity index and the non-radial direct distance function, this study improved the data envelopment analysis (DEA) model to evaluate the energy-saving and emissions-reduction performance (EEP) of these three urban agglomerations. The empirical results indicated that BTH did not show improvement in performance, whereas YRD and PRD showed a significant improvement. The annual growth rate of performance was higher in the PRD than in the other two urban agglomerations. The "catch-up effect" of the three urban agglomerations vanished after 2010, and the possible reasons for this change are the large-scale economic stimulus plan adopted by the government to address the global crisis and the recent decline of economic growth. The technical progress level increased at first, then decline, and increased again. This study also found that β convergence of performance existed in BTH and YRD. However, there was no β convergence of performance in PRD. Highlights: The non-radial directional distance function is adopted to evaluate the EEP. The "catch-up effect" and technical progress do not always exist in 2005–2016. Pearl River Delta makes a significant improvement in EEP. There exists β convergence of performance in BTH and YRD, while not in PRD.